Barriers to Gait Training among Stroke Survivors: An Integrative Review - Eveline Tavares; Joana Coelho; Patrícia Rogado; Rita Correia; Cidália Castro; Júlio Belo Fernandes (Journal of Functional Morphology and Kinesiology, 2022)
Gait recovery is vital for stroke survivors’ ability to perform their activities associated with daily living. Consequently, a gait impairment is a significant target for stroke survivors’ physical rehabilitation. This review aims to identify barriers to gait training among stroke survivors. An integrative review was conducted following Whittemore and Knafl’s methodology. The research was carried out on the electronic databases Scopus, PubMed, and B-on, applying a time span of 2006 to 2022. A total of 4189 articles were initially identified. After selecting and analyzing the articles, twelve studies were included in the sample. This review allowed for the identification of several barriers to gait training among stroke survivors, which can be grouped into three categories: individual, environmental, and rehabilitation workforce-related barriers. These findings highlight that participation in gait training is not solely dependent on the stroke survivor. Instead, the uptake of rehabilitation programs may also depend on environmental and rehabilitation workforce-related factors.